Foreign object debris detection based on continuous wave forward scattering radar doppler effect - Munawar, Aris (2011)
Surveillance system has become necessity for many working areas such as civil, military, defense, security, industry, flight, etc. This research concerns about the using of radar to detect ground non-moving objects that become hazardous objects in a specified environment. These kinds of objects are usually known as Foreign Object Debris (FOD). Any unwanted objects lying on roads, bus ways, taxi ways, or the airplane runways can be categorized as FOD. Especially for flight, FOD has become a vital problem that can cause fatal damage or even an accident for an aircraft. This study is specially aimed to detect and localize the existence of FOD in a covered area using a special mode of bistatic radar system known as Forward Scattering Radar (FSR). The method is by analyzing the Doppler signal extracted from the received signal scattered by the target. The received signal comprises direct signal from the transmitter and scattered signal from the target, therefore by analyzing the Doppler signal at the receiver could give the information about the existing of target. This research is a development of the previous research which was Forward Scattering Radar for moving ground target detection. The difference between current research and the previous research is that in the previous research the Doppler shift is caused by the moving target, while in the current research the Doppler shift is created by intentionally moving the transmitter antenna. A hardware setup and an experimental scenario have been chosen to carry out this research. A transmitter antenna is set to move in an angular direction for scanning the covered area, while in the other side a receiver is located to receive the transmitted signal. An object – supposed to be the FOD – is then located between the transmitter and the receiver. The transmitter antenna is fed into a continuous wave signal generator and moved using a controlled stepper motor. While, the received signal at the receiver will be passed through a receiving circuit to extract its Doppler signal. A computer simulation in accordance with this experimental scenario is also designed to confirm the analysis result of this research. Any parameters used in the experimental will also be adopted in the computer simulation. An FSR formulation will be applied to perform this simulation. FOD detection will be performed both in time domain and frequency domain of the Doppler signal. A subtraction and statistical correlation of several no-target Doppler and with-target Doppler signals will be performed in this case. Both theoretical and experimental signals will be analyzed to confirm the result. The power – frequency extraction will be done using standard Fourier Transform. Analyses of FOD detection on time domain are done. Subtraction of with-target by no-target Doppler signals results on scattered Doppler signal, and the existing of this scattered Doppler signal has proven the existing of FOD. By performing cross correlation between no-target and with-target Doppler signals, a line plot of correlation coefficient is resulted. The average of correlation coefficient is significantly different compared to the cross correlation between no-target Doppler signals, and this is enough to conclude that the FOD does exist. While, analyses on frequency domain of those signals give proportional results as on time domain signals. FOD localization will be performed using the time-frequency analysis of the scattered Doppler signal. The existence of target will be represented by the existing of zero Doppler at the time-frequency characteristic of the scattered Doppler signal. FOD localization will be performed for both theoretical and experimental signal. An optimized Hilbert – Huang transform will be used to analyze the time-frequency properties of the signals. The elaboration about the Hilbert – Huang transform optimization will be discussed. By analyzing two different Doppler signals of different target location, different zero Doppler positions are identified. By relating the time position of zero Doppler with the angular velocity of transmitter antenna, the direction angle in which the target was located could be calculated.After all, this research will have contribution on introducing the theoretical and experimental system design of FSR for non-moving object detection. Moreover, this research also contributes on optimization of the existing well-known Hilbert-Huang Transform, by removing the cyclic error.